Finance and Development, September 1991. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1991)
We need to understand more deeply a number of critical issues that confront the World Bank and its member countries before we can transform knowledge into effective actions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet